Prospecção magnetométrica em intrusiva básica com indícios de mineralização aurífera no município de São Sepé - RS - Pereira, Alice Marques [UNESP] (2014)
This study consists of the acquisition of geophysical data by means of terrestrial magnetometry, in an area with evidence of gold and sulfide mineralization, located in the city of São Sepé, in the South of Brazil. The resulting data from the application of this method established a relation between the geophysical results with potential mineralized sites, from evidence obtained in a geochemical prospection of stream sediments that were previously developed. The Santa Catarina gabbro is intruded in the Vacacaí Metamorphic Complex, a metasedimentary sequence where many gold deposits were found. In this study, there were nine lines of terrestrial magnetometry, each one being 1,200 m long, for a total of 10,800 m and 720 reading stations. The magnetometric products generated were, the total field maps, the analytic signal amplitude, and regional and residual maps, in which the average radial power spectrum allowed the selection of the wave number interval, suited for the components separation in shallow and deep, and this was later correlated with geological data and previous studies. The obtained results suggest that due to metalogenetic processes that might have controlled the mineral genesis, the magnetic anomalies were indirectly related to the auriferous mineralization